Cycles of vascular plexus formation within the nephrogenic zone of the developing mouse kidney - David A. D. Munro (Nature Portfolio, 2017)
Abstract The renal vasculature is required for blood filtration, blood pressure regulation, and pH maintenance, as well as other specialised kidney functions. Yet, despite its importance, many aspects of its development are poorly understood. To provide a detailed spatiotemporal analysis of kidney vascularisation, we collected images of embryonic mouse kidneys at various developmental time-points. Here we describe the first stages of kidney vascularisation and demonstrate that polygonal networks of vessels (endothelial plexuses) form in cycles at the periphery of the kidney. We show that kidney vascularisation initiates at E11, when vessels connected to the embryonic circulation form a ring around the ureteric bud. From E13.5, endothelial plexuses organise around populations of cap mesenchymal and ureteric bud cells in a cyclical, predictable manner. Specifically, as the ureteric bud bifurcates, endothelia form across the bifurcation site as the cap mesenchyme splits. The plexuses are vascular, carry erythrocytes, are enclosed within a basement membrane, and can always be traced back to the renal artery. Our results are a major step towards understanding how the global architecture of the renal vasculature is achieved.